PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - LISETT LISETT; Julisar Julisar (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of corporate social responsibility (CSR), executive character, predictability capital intensity, leverage, sales growth, council independent commissioner, firm size, and audit committee on financial tax avoidance.The objects used in this study are manufacture companies listed on the Indonesia Stock Exchange for 3 years from 2018 to 2020. The objects were obtained using the purposive sampling method, there were 57 manufacture companies listed on the Indonesia Stock Exchange which were used as the sample in this study. Hyphotesis testing and data analysis in this study was carried out using multiple linear regression models.The results of this study showed that the executive character, profitabilitas, capital intensity, leverage, sales growth, council independent commissioner, firm size, and audit committee have no effect on the tax avoidance, which means that these variables occur because of restrictions on tax avoidance by the company. Meanwhile, corporate social responsibility (CSR) and firm size affect tax avoidance, which means that these variables have the possibility of tax avoidance by the company.